Structural, optical and photocatalytic properties of zinc oxides obtained from spent alkaline batteries - Gallegos, María Victoria (2018)
The structural, optical and photocatalytic properties of two zinc oxides prepared from spent alkaline batteries were analysed. After leaching the anode of alkaline batteries, zinc was precipitated from the leachate liquor by introducing oxalic acid (O-ZnO) or sodium carbonate (C-ZnO). The structure of ZnO samples were analysed by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), SBET, DRS-UV-vis spectroscopy and positron annihilation lifetime spectroscopy (PALS). Both oxides present the ZnO wurzite structure and similar morphology. C-ZnO presents a cell lower lattice parameters and bang gap energy (2.99 eV) than O-ZnO (3.05 eV), possibly due to higher concentration of oxygen vacancies. The photocatalytic activity in the degradation of methylene blue (MB) of O-ZnO (achieving 70% MB degradation at 90 min) was superior to C-ZnO, due to its higher surface area and degree of crystallinity and lower bulk/surface defects ratio.